Eicosanoid Metabolomic Profile of Remdesivir Treatment in Rat Plasma by High-Performance Liquid Chromatography Mass Spectrometry - Du, Ping; Wang, Guo-yong; Zhao, Rui; An, Zhuo-ling; Liu, Li-hong (Frontiers in Pharmacology, 2021)
Remdesivir, a nucleotide analog prodrug, has displayed pharmacological activity against SARS-CoV-2. Recently, eicosanoids are widely involved in regulating immunity and inflammation for COVID-19 patients. Rats were intravenously administered remdesivir at a dose of 5 mg/kg, and series of blood samples were collected before and after treatment. Targeted metabolomics regarding the eicosanoid profile were investigated and quantitated simultaneously using the previously reported reliable HPLC-MS/MS method. Additionally, interplay relationship between metabolomics and pharmacokinetic parameters was performed using the Pearson correlation analysis and PLS model. For the longitudinal metabolomics of remdesivir, metabolic profiles of the same rat were comparatively substantial at discrete sampling points. The metabolic fingerprints generated by individual discrepancy of rats were larger than metabolic disturbance caused by remdesivir. As for the transversal metabolomics, the prominent metabolic profile variation was observed between the baseline and treatment status. Except for TXB2, the inflammatory- and immunology-related eicosanoids of resolvin D2, 5-HEPE, 5-HETE, and DHA were significantly disturbed and reduced after single administration of remdesivir (p < 0.05, p < 0.001). Moreover, the metabolite of PGE2 correlated with GS-441524 (active metabolite of remdesivir) concentration and pharmacokinetic parameters of Cmax, AUC0-t, AUC0-infinity, and CL significantly. Eicosanoid metabolic profiles of remdesivir at both longitudinal and transversal levels were first revealed using the robust HPLC-MS/MS method. This initial observational eicosanoid metabolomics may lighten the therapy for fighting COVID-19 and further provide mechanistic insights of SARS-CoV-2 virus infection.